2013
DOI: 10.1371/journal.pone.0083751
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Cobalt Causes Transcriptomic and Proteomic Changes in Two Rat Liver Derived Cell Lines

Abstract: Cobalt is a transition group metal present in trace amounts in the human diet, but in larger doses it can be acutely toxic or cause adverse health effects in chronic exposures. Its use in many industrial processes and alloys worldwide presents opportunities for occupational exposures, including military personnel. While the toxic effects of cobalt have been widely studied, the exact mechanisms of toxicity remain unclear. In order to further elucidate these mechanisms and identify potential biomarkers of exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 56 publications
0
33
0
1
Order By: Relevance
“…Similarly, the minimum Cd concentrations required to induce mild toxicity in the rat cochlea was around 100 lM, much higher than that seen in vivo (Liu et al 2014). Another study reported using concentrations of Co up to 310 lM to examine biomarker gene changes induced by Co in H4-II-E-C3, a rat hepatoma cell line (Permenter et al 2013). One factor that is likely to account for in vivo versus in vitro differences toxicity is the duration of Co exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the minimum Cd concentrations required to induce mild toxicity in the rat cochlea was around 100 lM, much higher than that seen in vivo (Liu et al 2014). Another study reported using concentrations of Co up to 310 lM to examine biomarker gene changes induced by Co in H4-II-E-C3, a rat hepatoma cell line (Permenter et al 2013). One factor that is likely to account for in vivo versus in vitro differences toxicity is the duration of Co exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Based on its toxicity and long-term stability in the environment as well as its high probability score, a study by the Department of Defense rated CoCl 2 as having the highest toxicity potential among a subclass of 36 pure elements and metal compounds used in industry including toxic compounds such as arsenic, lead oxide, mercuric nitrate, mercury, and cadmium (Sutto 2011;Permenter et al 2013). The LD50 value for soluble Co salts has been estimated to be & Jerome A.…”
Section: Introductionmentioning
confidence: 99%
“…3). The recent report of gene expression analyses in rat liver cell lines by microarray and mass spectrometry approaches suggested that cobalt chloride modulates expression of gene sets primarily regulated by hypoxia and oxidative stress (39). Our results are consistent with this report and provide direct evidence for upregulation of Nrf2-regulated gene expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Its downstream target genes, pathways and proteins can regulate the cell response due to a hypoxia-like stimulation [20]. HIF-1 is composed of the HIF-1α and HIF-1 β subunits; the latter is constitutively expressed in the nucleus, whereas HIF-1α is regulated by the environment [2123].…”
Section: Introductionmentioning
confidence: 99%